2022
DOI: 10.3389/fpls.2022.953459
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of C2H2 zinc-finger gene family provides insight into the mechanisms and evolution of the dehydration–rehydration responses in Physcomitrium and Arabidopsis

Abstract: Dehydration tolerance is a vital factor for land plant evolution and world agricultural production. Numerous studies enlightened that the plant-specific C2H2-type zinc-finger proteins (C2H2-ZFPs) as master regulators played pivotal roles in the abiotic stress responses of plants. However, a comprehensive understanding of the evolution of C2H2-ZFPs in terrestrial plants and its regulatory mechanism in dehydration and rehydration response remains a mystery. In this study, the genome-wide identification of C2H2-Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 102 publications
1
2
0
Order By: Relevance
“…This is possible because often there is a balance between different SSPs (Kawakatsu et al, 2010). Similar to our data, where both starch and protein content are affected, opaque3 mutants have decreased protein content and reduced starch accumulation in rice endosperm (Cao et al, 2022). To further support the direct regulation of SSPs by ZOS5-09, we have shown that ZOS5-09 binds to the ZF_BS in the promoter of GLU6 (Fig.…”
Section: The Direct Effect Of Zos5-09 On Ssp Biosynthesissupporting
confidence: 88%
See 1 more Smart Citation
“…This is possible because often there is a balance between different SSPs (Kawakatsu et al, 2010). Similar to our data, where both starch and protein content are affected, opaque3 mutants have decreased protein content and reduced starch accumulation in rice endosperm (Cao et al, 2022). To further support the direct regulation of SSPs by ZOS5-09, we have shown that ZOS5-09 binds to the ZF_BS in the promoter of GLU6 (Fig.…”
Section: The Direct Effect Of Zos5-09 On Ssp Biosynthesissupporting
confidence: 88%
“…In addition, they also play important roles in biotic and abiotic stresses (Jiang and Pan, 2012, Han et al ., 2020). Till now, 189 C 2 H 2 ZF proteins have been reported in Oryza sativa (Agarwal et al ., 2007), 122 in Triticum durum (Faraji et al ., 2018), 321 in Glycine max (Yuan et al ., 2018a), 301 in Brassica rapa (Alam et al ., 2019), 104 in Solanum lycopersicum (Hu et al ., 2019), 218 in Medicago truncatula (Jiao et al ., 2020), 129 in Cucumis sativa (Yin et al ., 2020), 79 in Solanum tuberosum (Liu et al ., 2020), 98 in Vitis vinifera (Arrey-Salas et al ., 2021) and 158 in Arabidopsis thaliana (Li et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The cis-acting elements of the ZmC2H2 members showed that they had functions related to hormones, stress, and seed germination. As a transcription factor family, C2H2 members have been reported to have a connection with abiotic stresses, such as cold, heat, and drought [ 59 , 60 ]. Moreover, the cis-acting elements also contain hormone-related cis-acting elements, such as salicylic acid (SA), jasmonic acid (JA), ethylene (ET), and abscisic acid (ABA), in the C2H2 members’ promoter in poplar ( Populus trichocarpa ) and ginseng ( Panax ginseng ) [ 49 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…C2H2-type ZFPs, also known as TFIIIA-type zinc fingers, are among the most extensively studied and abundant ZFPs in eukaryotes [7]. Recently, the in silico genome-wide identification and functional characterization of plant C2H2-type ZFPs were well analyzed in many species, including 321 members in Glycine max [8], 301 in Brassica rapa [9], 218 in Medicago truncatula [10], 204 in Triticum aestivum [11], 189 in Oryza sativa [12], 176 in Arabidopsis thaliana [13], 150 in Zea mays [14], 145 in Sorghum bicolor [15], 129 in Cucumis sativus [16], 109 in Populus trichocarpa [17], and 104 in Solanum lycopersicum [18]. These findings indicate that C2H2 ZFPs are ubiquitous in the plant kingdom, playing important regulatory roles in various biologic processes, including development and organogenesis, as well as responses to stresses and defense.…”
Section: Introductionmentioning
confidence: 99%